2013
DOI: 10.1088/0953-8984/25/48/485501
|View full text |Cite
|
Sign up to set email alerts
|

Electric and magnetic field effects on the excitonic properties of elliptic core–multishell quantum wires

Abstract: Abstract. The effect of eccentricity distortions of core-multishell quantum wires on their electron, hole and exciton states is theoretically investigated. Within the effective mass approximation, the Schrödinger equation is numerically solved for electrons and holes in systems with single and double radial heterostructures, and the exciton binding energy is calculated by means of a variational approach. We show that the energy spectrum of a core-multishell heterostructure with eccentricity distortions, as wel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…14,15 Previous papers in the literature have theoretically demonstrated that the main effect of such hexagonal geometry was an increase of the carriers concentration around the corners of the hexagonal confining shell. 16 Similar effect is also observed for an elliptic shell, where carriers concentrate in the regions of higher curvature; 17,18 (ii) Heavy hole-Light hole coupling and band mixing effects are neglected-this is an usual and fair approximation 19,20 that simplifies a lot the calculations, by avoiding the need to diagonalize a valence band matrix, which is a very time consuming procedure; (iii) The dielectric mismatch effect between the different layers and between the outmost shell and the vacuum are neglected. In fact, the former is not expected to have a significant contribution, since this effect is proportional to 1 À 1 = 2 , 21 where 1 and 2 are the dielectric constants of the Si core and Si 0.7 Ge 0.3 shell, respectively, which are very similar.…”
Section: Theoretical Modelsupporting
confidence: 56%
“…14,15 Previous papers in the literature have theoretically demonstrated that the main effect of such hexagonal geometry was an increase of the carriers concentration around the corners of the hexagonal confining shell. 16 Similar effect is also observed for an elliptic shell, where carriers concentrate in the regions of higher curvature; 17,18 (ii) Heavy hole-Light hole coupling and band mixing effects are neglected-this is an usual and fair approximation 19,20 that simplifies a lot the calculations, by avoiding the need to diagonalize a valence band matrix, which is a very time consuming procedure; (iii) The dielectric mismatch effect between the different layers and between the outmost shell and the vacuum are neglected. In fact, the former is not expected to have a significant contribution, since this effect is proportional to 1 À 1 = 2 , 21 where 1 and 2 are the dielectric constants of the Si core and Si 0.7 Ge 0.3 shell, respectively, which are very similar.…”
Section: Theoretical Modelsupporting
confidence: 56%
“…In other words, the laser field creates an anisotropy in the confinement potential, which can be continuously controlled by the THz laser field. It is useful to compare our results with those for elliptic core–multishell quantum wires 40 and CDQRs 41 . In these works, the anisotropy was induced by the geometry of the structure, that needs to be controlled during the growth process 40 or by effective mass 41 manipulations.…”
Section: Problemmentioning
confidence: 99%
“…These devices have also gained much importance because their properties are tailorable, thanks to technological advances in controlled growth and fabrication [5,6]. The different geometries of such structures [7][8][9][10][11][12] and different material compositions [13][14][15][16] further add to the novelty in their performance. The distinctive difference in their properties from those of bulk structures is due to the quantization of energy states [17,18], and hence characteristically different density states.…”
Section: Introductionmentioning
confidence: 99%